Inhibition Test of Browning Reaction in Apple (Malus domestica Borkh.) by Low NaCl Concentration - Maulana Yusuf; Anang Mohamad Legowo; Ahmad Ni'matullah Al-Baarri (Journal of Applied Food Technology, 2018)
Reaction of enzymatic browning in fruit is a reaction that occurs due to the oxidation of phenol and involves the enzyme polyphenol oxidase (PPO). Prevention of browning reactions can be done by inhibiting PPO activity, one of alternative is to use NaCl. The purpose of this study was to determine the ability of low NaCl concentration to inhibit the browning reaction based on the color change of L* value. Apple peels was dipped in phosphate buffer pH 7.0 containing 0.1 M NaCl and incubated at room temperature for 6 hours. The result indicated the hindrance of NaCl in the development browning color that was detected by L* value. In conclusion, NaCl may inhibit the process of browning apple in room temperature.